2021
DOI: 10.1186/s13578-021-00693-3
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening causes distinct cell division regimes during replicative senescence in Saccharomyces cerevisiae

Abstract: Background Telomerase-negative cells have limited proliferation potential. In these cells, telomeres shorten until they reach a critical length and induce a permanently arrested state. This process called replicative senescence is associated with genomic instability and participates in tissue and organismal ageing. Experimental data using single-cell approaches in the budding yeast model organism show that telomerase-negative cells often experience abnormally long cell cycles, which can be foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…The mathematical model is largely based on our data from single cell lineages observed in microfluidic experiments and accounts for a number of already well-characterized types of cell-to-cell variability, as described in ( 16, 18, 24 ). In the microfluidic experiments, the consecutive cell cycle durations are measured from telomerase inactivation to cell death in individual cell lineages (Fig.1B-C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mathematical model is largely based on our data from single cell lineages observed in microfluidic experiments and accounts for a number of already well-characterized types of cell-to-cell variability, as described in ( 16, 18, 24 ). In the microfluidic experiments, the consecutive cell cycle durations are measured from telomerase inactivation to cell death in individual cell lineages (Fig.1B-C).…”
Section: Resultsmentioning
confidence: 99%
“…S1B-D). The probabilities to exit a sequence of arrests (𝑝 /.0-&/ and 𝑝 ).-( 1) were assumed to be constant, as demonstrated (24). For senescence onset, 𝑝 ,.'…”
Section: Calibration Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, other researchers have reported that replicative senescence can be distinguished from induced senescence by analyzing rDNA or methylation of its promoter 41) . Telomerase shortening, the main phenotype of cell replication, is thought to be the main trigger for inducing replicative senescence 42,43) . Recently, various studies have shown that telomere shortening causes constant DNA damage response, leading to stress-induced premature senescence 44) .…”
Section: Discussionmentioning
confidence: 99%